The Pragmatic Strategies of Impoliteness Within Instagram Comment Sections (On The Discourse Surrounding Prabowo Subianto’s Speeches During The 2024 Political Cycle) - Andreka Septiawan; Jihan Alayya; Tyara Ramadhani Safitri; Zahra Nurhaliza (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the pragmatic strategies of impoliteness within Instagram comment sections, focusing on the discourse surrounding Prabowo Subianto’s speeches during the 2024 political cycle. As digital interaction reshapes communication, this research moves beyond simple categorisations of hostility to explore the "cyberpragmatics" of political interaction. Analysing interactions on official posts and foreign media reportages, specifically The Straits Times, this research identifies a divergence in linguistic behaviour rooted in "cultural blindness" and "ambient affiliation." At the same time, domestic discourse utilises sarcasm and meme-based humour; interactions with international media trigger distinct impoliteness strategies to enforce national face-saving mechanisms. Utilising Culpeper’s impoliteness framework and supporting studies on online animosity, the study reveals that Indonesian netizens employ bald-on-record impoliteness and weaponised irony to insulate political figures from external critique. The findings suggest that digital impoliteness is not merely a lack of etiquette but a structured identity-building strategy, or "homophily," in which aggression serves to bond the in-group against perceived out-groups.